Музеєфікація пам’яток архітектури та містобудування як засіб збереження історико-культурної спадщини - Брич, Марія (Publishing House of Lviv Polytechnic National University, 2015)
Проаналізовано світовий і вітчизняний досвід музеєфікації історико-культурної спадщини. Висвітлено проблеми збереження пам’яток архітектури та містобудування – як ансамблевих та середовищних пам’яток, так і окремих об’єктів та споруд, їх поєднання з регіоном, суспільством і оточенням. Досліджено стан використання об’єктів архітектурної спадщини, що належать до музейного простору України. Запропоновано метод збереження пам’яток шляхом музеєфікації з метою максимального збереження та виявлення їхньої історико-культурної, наукової, художньої цінності. Historical and cultural heritage of Ukraine is very diverse. But many monuments today are in ruins and not used. Sometimes it is not possible to return to the monument its original function, which creates the need to find new applications. Therefore, the most effective method of attracting the cultural space of Ukraine is museumfication. Museumfication is to convert historical, cultural or natural objects into a museum display objects for preservation and identification of historical, cultural, scientific and artistic value. This is a set of evidence-based measures to bring objects of cultural heritage in the state fit for sightseeing visits. Ukraine already has experience in museumfication of the archaeological monuments, often inseparably linked with the environment and surrounding monuments of architecture and urban planning. Such complexes and ensembles are impossible to perceive, taking each individual object. It is important to consider them in the context of their original appearance and existence. The whole region, where there are several nearby monuments of architecture or town planning, needed to be seen as the holistic museum. That is why, it is much easier and more efficient to create historical, cultural and architectural reservation, organize museum-reserves based on architectural monuments. Creating large regional associations based on the museum-reserves significantly increase their exposure area and expand the functions and structure of the reservations and provide a tour visiting of remote museums, along with promotion of them. Unfortunately, the current socio-cultural situation in Ukraine is not conducive to the development of the museum network. Problem of inclusion of fallen monuments of architecture and urban planning to modern life remains unresolved. This article aims to draw attention to this problem and to propose a method of museumification for preservation and use of monuments.
Keywords: музеєфікація; історико-культурна спадщина; пам’ятка архітектури; пам’ятка містобудування; збереження пам’яток; museumfication; historical and cultural heritage; monument of architecture; monument of urban planning; preservation of monuments